Determinants of Teacher Performance at State Vocational School 1 Plupuh, Sragen District - Budisantoso, Dwiyono; Sudarwati, Sudarwati; Pawenang, Supawi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The aim of this research is to: (1) Find out the influence of commitment on the performance of educators at SMK Negeri 1 Plupuh Sragen Regency (2) Find out the influence of organizational culture on the performance of educators at SMK Negeri 1 Plupuh Sragen Regency (3) Find out the influence of supervision on the performance of educators at SMK Negeri 1 Plupuh Sragen Regency. (4) Knowing the effect of integrity on the performance of educators at SMK Negeri 1 Plupuh Sragen Regency. The research was conducted for 3 months, from April – August 2025, taking place at SMK Negeri 1 Plupuh, Sragen Regency. The population in this study was 53 educators, while the sample used was a population of 37 educators. Data collection techniques were carried out through observation, interviews, documentation, questionnaires and literature study. Data processing techniques were carried out using the SPSS program to carry out instrument tests (validity tests and reliability tests), multiple linear regression tests, classical assumption tests (normality tests, heteroscedasticity tests, and multicollinearity tests), hypothesis tests (F test and t test), and determination tests (R2). commitment, organizational culture, supervision and integrity have a significant influence on the performance of educators. Based on the determinant test, the adjusted R square value is 0.760. This means that the variables of commitment, organizational culture, supervision and integrity contribute to educator performance by 76.0%, while the remaining 24.0% is explained by other variables not proposed in this research